2019
DOI: 10.3390/jcm8101617
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Inhibitory Clindamycin and Azithromycin reduce S. aureus Exoprotein Induced Toxicity, Inflammation, Barrier Disruption and Invasion

Abstract: Background: Chronic rhinosinusitis (CRS) is defined as a chronic inflammation of the nose and paranasal sinus mucosa associated with relapsing infections—particularly with S. aureus. Long-term treatments with protein synthesis inhibitor antibiotics have been proposed to reduce inflammation in the context chronic severe inflammatory airway pathologies, including CRS. This study assessed the effect of subinhibitory clindamycin and azithromycin on S. aureus exoprotein induced inflammation, toxicity and invasivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…The decreased production of IL‐8 from HSNECs treated with azithromycin corroborates other published studies showing the anti‐inflammatory effect of macrolides including azithromycin in vitro and in vivo 37 . Moreover, a recent study identified that sub‐inhibitory azithromycin may also reduce Staphylococcus aureus exoproteins that induce pro‐inflammatory cytokines from HSNECs 38 . In a study using primary nasal polyp epithelial cells, several macrolides reduced the production of IL‐8 under Escherichia coli serotype 055:85 LPS‐stimulation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The decreased production of IL‐8 from HSNECs treated with azithromycin corroborates other published studies showing the anti‐inflammatory effect of macrolides including azithromycin in vitro and in vivo 37 . Moreover, a recent study identified that sub‐inhibitory azithromycin may also reduce Staphylococcus aureus exoproteins that induce pro‐inflammatory cytokines from HSNECs 38 . In a study using primary nasal polyp epithelial cells, several macrolides reduced the production of IL‐8 under Escherichia coli serotype 055:85 LPS‐stimulation.…”
Section: Discussionsupporting
confidence: 88%
“…37 Moreover, a recent study identified that sub-inhibitory azithromycin may also reduce Staphylococcus aureus exoproteins that induce pro-inflammatory cytokines from HSNECs. 38 In a study using primary nasal polyp epithelial cells, several macrolides reduced the production of IL-8 under Escherichia coli serotype 055:85 LPS-stimulation. CRS patients with nasal polyps (CRSwNP) showed reduced polyp size and lower IL-8 levels in nasal lavage following treatment with macrolide antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al . found that 1/2 MIC of clindamycin (0.1 μg/mL) but not azithromycin (1 μg/mL) results in the loss of the invasive capacity of S. aureus ATCC® 51650™ to enter primary human nasal epithelial cells; the infection rate of antibiotic-treated bacteria is 6.3% ± 0.76%, whereas that of bacteria without antibiotic treatment is 49% ± 9.8% [36] . In some cases, the sub-MICs of antibiotics that promote S. aureus adhesion capacity do not correlate well with bacterial invasion capability.…”
Section: Effects Of Sub-mics Of Antibiotics On the Adhesion And Invasion Of S Aureusmentioning
confidence: 98%
“…S. aureus can invade and propagate in mammalian cells [36] . After adhesion, subsequent invasion may occur during the infection of suitable host cells by S. aureus .…”
Section: Effects Of Sub-mics Of Antibiotics On the Adhesion And Invasion Of S Aureusmentioning
confidence: 99%
“…It has been demonstrated that S. aureus is able to penetrate the barrier of the columnar epithelium of the paranasal sinuses, thus enhancing the inflammatory process [ 9 , 10 ]. In this issue of JCM, Hu et al [ 11 ] studied the effects of sub-inhibitory clindamycin and azithromycin on the production of S. aureus exoproteins and the ensuing effect of decreasing inflammation, epithelial barrier disruption and invasion. The study was performed on primary human nasal epithelial cells (HNECs) from patients undertaking endoscopic skull base techniques without clinical or radiological evidence of CRS.…”
mentioning
confidence: 99%